The admissibility of child evidence in Malaysia / Mohd Azree Ezuan Saw, Amanda Putri Zainal Abidin and Mohamad Nasruddin Ab Rahman - Ezuan Saw, Mohd Azree; Zainal Abidin, Amanda Putri; Ab Rahman, Mohamad Nasruddin (2014)
Children are the important group of people that must be protected by the country. Their right as a citizen in this country must be protected and recognized by the judicial system. Under Section 134 of the Malaysian Evidence Act 1950, it was stated that the evidence of one witness will be enough to secure a verdict in criminal case or judgment in civil case. However, it is stated under Section 133A of Evidence Act 1950 whereby corroboration is required as a matter of law in determining the evidence of the child. Corroboration means an evidence that confirms or supports a statement, theory, or finding confirmation. Under this section, a child evidence may be taken if it sworn or unsworn evidence. Unsworn evidence is evidence that is given without the obligation of an oath first being taken or an affirmation being made. That means, child evidence could be readily admitted in any criminal trial, if it is proved the child is sufficiently intelligent to understand the meaning of. an oath and appreciates the consequences of an oath. Thus, this research will be discussed from the legal views, cases and also expert's opinion on the admissibility of child evidence under Section 133A of the Evidence Act 1950. This research will discussed on the procedure to determine the whether a child is sufficiently intelligent or understand the meaning of an oath. This research also will compare and contrast the admissibility of child evidence in Australia and United Kingdom. Recommendations and opinions from experts are provided in this research to amend this Section.